Inflammatory pseudotumour of the mouth and maxilla. Issue 2 (February 1996) - Shek, A W; Wu, P C; Samman, N
Abstract : AIM: To describe the clinicopathological and immunophenotypical findings of two cases of inflammatory pseudotumour in the oral cavity. METHODS AND RESULTS: The patients presented with a short history of swelling in the cheek and the maxilla respectively. Magnetic resonance imaging or computerised tomography scan showed space occupying lesions with infiltrative margins which were interpreted as aggressive malignant neoplasms. Histological examination showed fascicles of spindle cells in a background of chronic reactive inflammatory cells including plasma cells, typical of inflammatory pseudotumour. The spindle cells were positive for vimentin, smooth muscle actin and CD68, but were negative for follicular dendritic cell markers. The lymphocytes showed no light chain restriction. CONCLUSIONS: Inflammatory pseudotumour in the oral cavity is completely benign and simple excision is curative. However, it may be confused with a malignant tumour on clinical and radiographic grounds, and histologically the appearances can also be misinterpreted as those of a more aggressive lesion. Its correct recognition by the surgical pathologist is important to avoid unnecessarily radical and potentially mutilating surgery.